A high thermal conductivity erbium-doped β-phase gallium oxide laser crystal and its preparation method and use

By using the laser heating base method to grow high thermal conductivity Er3+ doped and co-doped Eu3+ ions in β-Ga2O3 crystals, the problems of low thermal conductivity and low conversion efficiency of existing mid-infrared laser materials are solved, and an efficient laser output in the 2.5-3.0μm band is achieved.

CN118727144BActive Publication Date: 2025-04-01YANCHENG INST OF TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410754351.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-12
Publication Date
2025-04-01
Estimated Expiration
2044-06-12

AI Technical Summary

Technical Problem

The existing 2.6-3μm mid-infrared laser materials have problems such as large phonon energy, low thermal conductivity, low conversion efficiency, and obvious crystal thermal lensing effects, resulting in high quantum loss of laser oscillation and serious material damage.

Method used

The laser heating base method is used to grow high-thermal conductivity Er3+ doped β-Ga2O3 crystals, and deactivated ion Eu3+ is incorporated into the β-Ga2O3 crystals to solve the blockage of the energy level under the laser channel of the Er3+ four-level system.

Benefits of technology

The laser characteristics of high thermal conductivity, low phonon energy, moderate doping concentration and high optical transmissibility are achieved, and the output efficiency of the 2.5-3.0μm band laser is improved, and the quantum efficiency reaches more than 85%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118727144B_ABST
    Figure CN118727144B_ABST
Patent Text Reader

Abstract

The invention discloses a high thermal conductivity erbium-doped β-phase gallium oxide laser crystal and a preparation method and application thereof. The invention utilizes a laser heating pedestal method to grow a high thermal conductivity Er 3+ Doping β-Ga2O3 crystals solves the problem of β-Ga2O3 single crystal growth. In addition, deactivation ions Eu are co-doped into β-Ga2O3 crystals. 3+ Solve Er 3+ ( 4 I 11 / 2 → 4 I 13 / 2 ) The lower energy level of the four-level system laser channel is blocked. The high thermal conductivity gallium oxide laser crystal has laser characteristics such as moderate doping concentration, low phonon energy, and high thermal conductivity. It can be used as a mid-infrared laser material in the 2.6‑3μm band in all-solid-state lasers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solid laser crystal materials, and in particular relates to a high thermal conductivity erbium-doped beta-phase gallium oxide laser crystal and a preparation method and application thereof. Background Art

[0002] 2.6-3μm mid-infrared lasers have important applications in the fields of medicine, communications, remote sensing, bioengineering, pollution monitoring, etc. At present, in the research of mainstream laser gain medium materials in the 2.6-3μm band, inorganic materials doped with rare earth ions are one of the main ways to obtain near-infrared and mid-infrared lasers. Most lanthanide rare earth ions have rich energy level structures, among which Er 3+ Rare earth ions 4 I 11 / 2 → 4 I 13 / 2 Energy level jump can produce laser in the 2.5-3.0μm band. 3+ The 2.7μm mid-infrared laser material for the luminescence center is mainly Er 3+ Single doped garnet structure aluminates, gallates, perovskite structure YAlO3, fluorides and ceramics. However, these matrix materials generally have defects such as large phonon energy, low thermal conductivity, low conversion efficiency and obvious crystal thermal lens effect. For example: Er 3+ pass 4 I 15 / 2 → 4 I 11 / 2 → 4 I 13 / 2 The quantum loss of the 2.6-3μm laser oscillation achieved by the Er transition is as high as 70%. This means that the laser oscillation has serious thermal effects and low conversion efficiency. 3+ Under high-concentration doping conditions, excessive heat is often deposited in a smaller section of the crystal, further exacerbating the thermal problems of the laser system and resulting in serious material damage. 3+ Doped (30-50at.%) YAG crystal is currently the most widely used laser material in 2.6-3μm band laser research. However, the upper energy level lifetime of Er:YAG is extremely short, and the thermal conductivity is only 13W / (m·K). In addition, the phonon energy of YAG is relatively high, which increases the probability of multi-phonon relaxation of laser upper energy level particles to laser lower energy level. Therefore, in Er:YAG crystal, to obtain effective CW laser output, Er 3+ The doping concentration often needs to reach 50% to effectively solve the laser energy level 4 I 13 / 2 Particle number blocking problem.

[0003] Gallium oxide Ga2O3 belongs to the monoclinic system. There are 6 known Ga2O3 crystal phases, including 5 stable phases such as α, β, γ and 1 transient phase κ-Ga2O3. Among them, the β phase is the thermodynamically stable phase Ga2O3 with a melting point of about 1785℃. At high temperatures, other phases are transformed into β-Ga2O3. For single crystal laser gain media, the thermal conductivity of β-Ga2O3 can reach 27.9W / (m·K), which is twice that of the most widely used YAG crystal. In addition, β-Ga2O3 single crystal has good chemical stability, is not corroded by strong acids and alkalis, has high mechanical strength, and has stable performance at high temperatures. Therefore, β-Ga2O3 single crystal has almost all the characteristics required for laser crystals and is a laser matrix material with great application prospects. At present, β-Ga2O3 is mainly used in high-power semiconductor devices and deep ultraviolet optoelectronic devices. So far, there has been no report on its application in the mid-infrared band. In addition, in the process of preparing β-Ga2O3 by the traditional melt method, the temperature gradient at the crystal growth interface is small, and the thermal radiation rate at the center of the interface is faster than the thermal radiation rate around it, resulting in the problem that the temperature at the center of the growth interface is high and the temperature around it is low, forming a concave growth interface. At this time, crystal defects such as cracking and spiral growth are prone to occur during the crystal growth process. The grown β-Ga2O3 single crystal has defects such as twinning, cracking, polycrystalline and spiral growth, and the β-Ga2O3 single crystal is difficult to process and is very easy to cleave. Summary of the invention

[0004] The main technical problem solved by the present invention is to provide a high thermal conductivity erbium-doped β-phase gallium oxide laser crystal and its preparation method and use. The present invention uses a laser heating base method to grow high thermal conductivity Er 3+ Doping β-Ga2O3 crystals solves the problem of growing β-Ga2O3 single crystal optical fibers. In addition, deactivation ions Eu are co-doped into β-Ga2O3 crystals. 3+ Solve Er 3+ ( 4 I 11 / 2 → 4 I 13 / 2 ) The lower energy level of the four-level system laser channel is blocked. The high thermal conductivity gallium oxide laser crystal has laser characteristics such as moderate doping concentration, low phonon energy, and high thermal conductivity. It can be used as a mid-infrared laser material in the 2.6-3μm band in all-solid-state lasers.

[0005] The present invention is implemented by the following technical solutions:

[0006] A method for preparing a high thermal conductivity erbium-doped β-phase gallium oxide laser crystal comprises the following steps: using Ga2O3 as a matrix material, Er2O3 and Eu2O3 as doping materials, preparing a source rod and a seed crystal, and then using a laser heating pedestal method to grow the high thermal conductivity erbium-doped β-phase gallium oxide laser crystal.

[0007] Furthermore, the specific steps for preparing the source rod and the seed crystal are as follows: first, the matrix raw material and the doping raw material are mixed together, and ground for 12-24 hours, and the ground raw material is sintered at 700-800 degrees in a muffle furnace for 5-10 hours, and then taken out and ball-milled again for 12-24 hours; the raw material is loaded into a rubber mold to make a round rod, and the round rod is placed in a cold isostatic press and kept at a pressure of 200Mpa for 5 minutes, and then the pressure is slowly released and taken out, the rubber mold is broken to take out the round rod, and then sintered at 1400-1500°C for 15-20 hours to obtain a material rod; in addition, one of the material rods is selected, one end is ground to a diameter of 0.4-1mm as a seed crystal, and the other material rod is used as a source rod.

[0008] Furthermore, the specific steps of the laser heating base method are as follows: fix the prepared source rod on the feeding device, and fix the prepared seed crystal on the upper pulling device; turn on the mechanical pump to perform vacuum treatment, and then fill the furnace with growth atmosphere, control the furnace to 0.03MPa, adjust the focus of the laser to fall on the top center of the source rod, set the laser program, increase the laser power to 60-100W within 15-20 minutes, melt the top of the source rod, and at the same time adjust the control system so that the center of the top cross section of the source rod is located at the laser reflection focus, continue to increase the power to 120-140W, so that it forms a stable hemispherical molten zone, and keep the temperature constant for 3-5 minutes; slowly lower the seed crystal, adjust the seed crystal to After the crystal is aligned with the center of the hemispherical molten zone of the source rod, it contacts the molten zone and stops descending. After keeping warm for 5-10 minutes, the pulling device is started and the laser power is increased to 145-155W for necking. When the diameter of the seed crystal shrinks to 0.3-0.5mm, the power is adjusted to 120-130W for shoulder release and equal-diameter growth. During the equal-diameter growth process, the seed crystal pulling speed is 40-60mm / h, and the source rod feeding speed is 6-10mm / h. When the crystal grows to the required size, the power is gradually increased to 200W, and the crystal is lifted off by continuing to pull. After the crystal growth is completed, the laser power is reduced at a rate of 5W / minute. After turning off the laser, the furnace is opened after 15 minutes of flowing air to remove the crystal.

[0009] Furthermore, the molar percentages of Er2O3 and Eu2O3 in the mixed raw material are 10-30 mol% and 0.1-1 mol%.

[0010] Furthermore, the purity of Ga2O3 is not less than 99.999%, and the purity of Er2O3 and Eu2O3 is not less than 99.99%.

[0011] Furthermore, during the isodiametric growth process, the ratio of the pulling speed to the feeding speed is 5-6:1.

[0012] Furthermore, before crystal growth, the seed crystal and the source rod were placed in anhydrous ethanol for cleaning for 10 minutes, and then placed in an oven for drying at 60° C. for 6 hours.

[0013] Furthermore, a high temperature annealing step is included, and the steps are as follows: the grown crystal is heated to 1200-1300° C. in a sintering furnace for high temperature annealing and kept at a constant temperature for 24-36 hours to eliminate thermal stress in the crystal and prevent cracking.

[0014] Furthermore, the growth atmosphere is pure oxygen.

[0015] Furthermore, the length of the material rod is 30-80 mm, and the diameter of the round rod is 1.5-2.0 mm.

[0016] The invention provides an erbium-doped beta-phase gallium oxide laser crystal with high thermal conductivity prepared by the method.

[0017] The present invention also provides the use of the high thermal conductivity erbium-doped beta-phase gallium oxide laser crystal, which is used in a mid-infrared laser.

[0018] Laser Heating Pedestal Method (LHPG) is a new single crystal optical fiber growth method. Figure 1 As shown in the figure, the laser is focused on the top of the source material rod to melt it and form a tiny melting zone that is not in contact with the container; then the end of the seed crystal is extended into the melting zone, and after it melts, the seed crystal is pulled out from the source rod at an appropriate speed in the opposite direction to grow a crystal. The laser heating pedestal method has many unique advantages, such as simple equipment structure, no crucible contamination during single crystal growth, easy diameter control, a wide range of growth materials, the ability to grow materials of different compositions, and a large temperature gradient in the growth zone. Although the laser heating pedestal method (LHPG) has many advantages, it is not easy to grow a single crystal fiber with good quality and ideal diameter, because it is affected by many factors in the process of obtaining the sample, such as the size, uniformity, mechanical properties, impurity concentration, viscosity, thermal conductivity, etc. of the powder rod during the preparation of the powder rod, and the laser power, pulling speed and feeding speed ratio during the growth process. The present invention optimizes the growth conditions of single crystal optical fiber and successfully grows single crystal optical fiber with a diameter of 600 μm and a length of 17.5 cm, with an aspect ratio of 290:1, no cracks, no bubbles, no impurities, high transparency, uniform diameter and good flexibility. In addition, the single crystal also has greatly enhanced fluorescence emission efficiency of 2.7 μm. 3+ and Eu 3+ The energy conversion efficiency reaches over 85%.

[0019] Beneficial effects of the present invention:

[0020] (1) The present invention uses LHPG technology to explore the growth process of β-Ga2O3 single crystal optical fiber. In the growth research, the problems of diameter fluctuation, crystal cracking, difficult processing, and easy cleavage of β-Ga2O3 crystal fiber grown at the concave interface of the traditional melt method are overcome, and finally a high-quality Er with a diameter of 600 μm is obtained. 3 / Eu 3+ Co-doped β-phase Ga2O3 single crystal optical fiber.

[0021] (2) The present invention 3 / Eu 3+ The co-doped β-phase gallium oxide laser crystal has low phonon energy (maximum phonon energy 658cm -1 ), high thermal conductivity (reaching 27.9W / (m˙K), twice that of the most widely used YAG crystal), high optical transmittance, small amount of color center formation, uniform diameter, relatively smooth surface, few bubbles, etc., which can effectively solve the problem of Er-doped in the 2.6-3μm band 3+ Laser crystals generally have a significant problem with thermal lens effect.

[0022] (3) With Er 3+ Compared with single doped crystal, the present invention doped Er into β-Ga2O3 single crystal 3+ and Eu 3+ Ions, co-doped Eu 3+ Deactivated ions, Eu 3+ of 7 F6 energy level and Er 3+ Lower energy level 4 I 13 / 2 close, can be achieved through cross relaxation (Er 3+ : 4 I 13 / 2 +Eu 3+ : 7 F6→Er 3+ : 4 I 15 / 2 +Eu 3+ : 7 F0(ET), such as Figure 2 As shown), so that Er 3+ Laser lower energy level 4 I 13 / 2 The lifetime of the particle beam is reduced, which results in de-excitation, thus achieving particle beam flipping and releasing the Er 3+ The limitation of the self-termination effect is beneficial to the output of laser in the 2.5-3.0um band and greatly improves the quantum efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings are used to provide further explanation of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0024] Figure 1 Schematic diagram of the crystal growth principle of the laser heated pedestal method (LHPG).

[0025] Figure 2 For Er 3+ and Eu 3+ A simplified diagram of the energy levels. DETAILED DESCRIPTION

[0026] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the following embodiments.

[0027] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0028] Example 1

[0029] A method for preparing a high thermal conductivity erbium-doped β-phase gallium oxide laser crystal comprises the following steps:

[0030] Selection and processing of material rods and seed crystals: Ga2O3 (purity 99.999%) is used as the matrix material, Er2O3 (purity 99.99%) and Eu2O3 (purity 99.99%) are used as doping materials. The matrix material and the doping material are mixed together and ground for 18 hours. The molar percentage concentrations of Er2O3 and Eu2O3 in the mixed material are 20 mol% and 0.4 mol%. The ground materials are sintered in a muffle furnace at 750 degrees for 8 hours. When the raw material is put into a rubber mold, it is taken out and ball-milled again for 18 hours; the raw material is put into a rubber mold to make a round rod, the round rod is put into a cold isostatic press and kept at a pressure of 200Mpa for 5 minutes, and then the pressure is slowly released and taken out, the rubber mold is broken to take out the round rod, and then sintered at 1450℃ for 20 hours to obtain a material rod, the length of the material rod is 80mm, and the diameter is 1.5mm; in addition, one of the material rods is selected, one end is ground to a diameter of 0.6mm, as a seed crystal, and the other material rod is used as a source rod;

[0031] Crystal growth of single crystal optical fiber; clean the lens, furnace cavity, plane reflector and focusing mirror in the optical system, adjust the optical system of the equipment so that the focused heating spot can be heated evenly, fix the prepared source rod on the feeding device, and fix the prepared seed crystal on the upper pulling device; turn on the mechanical pump to evacuate, and then fill the furnace with growth atmosphere (pure O2), control the furnace to 0.03MPa, adjust the focus of the laser to fall on the center of the top of the source rod, so that the top of the source rod can be evenly heated to form a molten zone with a stable shape, set the laser program, increase the laser power to 60-100W within 15-20 minutes, melt the top of the source rod, and at the same time adjust the control system so that the center of the top cross section of the source rod is located at the laser reflection focus, and continue to increase the power to 130W to form a stable Hemispherical melting zone, keep constant temperature for 4 minutes; slowly lower the seed crystal, adjust it so that the seed crystal is close to the center of the hemispherical melting zone of the source rod, and stay for 1 minute, then make it contact with the melting zone, and stop descending; after keeping warm for 5 minutes, the diameter of the seed crystal neither expands nor shrinks, start the pulling device, and gradually increase the laser power to 150W, and neck at a speed of 8mm / h; when the diameter of the seed crystal shrinks to 0.4mm, adjust the power to 125W, and carry out shoulder release and equal diameter growth; during the equal diameter growth process, the seed crystal pulling speed is 48mm / h, and the source rod feeding speed is 8mm / h. When the crystal grows to the required size, gradually increase the power to 200W, and continue to pull to lift the crystal; after the crystal growth is completed, reduce the laser power at a rate of 5W / min, turn off the laser, open the furnace after flowing air for 15 minutes, and remove the crystal. The grown crystal is then heated to 1250° C. in a sintering furnace for high temperature annealing and kept at a constant temperature for 30 hours to eliminate thermal stress in the crystal and prevent cracking.

[0032] This embodiment uses LHPG technology to grow single crystal optical fiber, so there is no need to use a crucible. Although pollution is reduced, the diameter of its crystal optical fiber will be affected by factors such as pulling speed, power fluctuation, and melting zone length. When these influencing factors exist, the optical fiber diameter will fluctuate, and the optical fiber diameter fluctuation will increase its transmission loss, thereby having a huge negative impact on its application. Therefore, it is very important to control the uniformity of the optical fiber diameter. By optimizing the growth conditions such as laser power, pulling speed and feed speed ratio, the diameter fluctuation of the single crystal optical fiber is characterized by real-time diameter monitoring. It is found that the optical fiber diameter fluctuation is extremely small, and the diameter fluctuation of the single crystal optical fiber is successfully optimized to within 3%, showing extremely high diameter uniformity. The diameter of the single crystal optical fiber obtained in this embodiment is 0.6mm and the length is 175mm. There are no large-size defects such as bubbles, holes and cracks inside it, and the original crystal phase is maintained. The rare earth ions are evenly distributed, proving the feasibility and reliability of the growth method.

[0033] In this embodiment, Er is doped into the β-Ga2O3 single crystal. 3+ and Eu 3+Ions, co-doped Eu 3+ Deactivated ions can cross-relax to make Er 3+ Laser lower energy level 4 I 13 / 2 The lifetime of the particle beam is reduced, which results in de-excitation, thus achieving particle beam flipping and releasing the Er 3+ The limitation of the self-termination effect is beneficial to the output of laser in the 2.5-3.0um band and greatly improves the quantum efficiency.

[0034] Example 2

[0035] As described in Example 1, except that the atomic percentages of Er2O3 and Eu2O3 in the mixed raw material are 25 mol% and 0.8 mol%, respectively, and the other steps and conditions are consistent with Example 1. The single crystal optical fiber obtained in this example has a diameter of 0.6 mm and a length of 174 mm, and the diameter fluctuation of the single crystal optical fiber is 3%.

[0036] Example 3

[0037] As described in Example 1, except that the atomic percentages of Er2O3 and Eu2O3 in the mixed raw material are 15 mol% and 0.2 mol%, respectively. Other steps and conditions are consistent with Example 1. The single crystal optical fiber obtained in this example has a diameter of 0.6 mm and a length of 170 mm, and the diameter fluctuation of the single crystal optical fiber is 3%.

[0038] Comparative Example 1

[0039] A method for preparing a single crystal optical fiber is as described in Example 1, except that the upper pulling speed during the equal-diameter growth process is 20 mm / h, and the other steps and conditions are consistent with Example 1.

[0040] In this comparative example, since the pulling speed is relatively too slow, the crystal diameter is too large, the growth time is prolonged, and it is affected by more thermal stress, resulting in thermal cracks. The large number of distributed cracks can no longer be removed normally. After the growth process is completed, when the crystal fiber is taken out of the melting zone, the existence of thermal cracks causes the crystal fiber to break directly in the furnace chamber. The diameter of the obtained single crystal optical fiber is 0.9mm, the diameter fluctuation is 7%, and the length before breaking is 107mm.

[0041] Comparative Example 2

[0042] A method for preparing a single crystal optical fiber is as described in Example 1, except that the upper pulling speed during the equal-diameter growth process is 30 mm / h, and the other steps and conditions are consistent with Example 1.

[0043] The crystal fiber of this comparative example can be taken out normally, but is full of cracks and will break even with a slight touch. The diameter of the obtained single crystal optical fiber is 0.7 mm, the diameter fluctuation is 6%, and the length is 132 mm.

[0044] Comparative Example 3

[0045] A method for preparing a single crystal optical fiber is as described in Example 1, except that the upper pulling speed during the equal-diameter growth process is 80 mm / h, and the other steps and conditions are consistent with Example 1.

[0046] In this comparative example, since the pulling speed is too fast, the stability of the solid-liquid interface is destroyed, the crystal is pulled out of the melt before the optimal growth conditions are reached, and the internal stress of the crystal is too large, resulting in cracks in the obtained crystal fiber and poor quality. The crystal fiber can be broken by a slight touch, and the diameter fluctuates significantly. The diameter of the obtained single crystal fiber is 0.3mm, the diameter fluctuation is 11%, and the length is 168mm.

[0047] Comparative Example 4

[0048] A method for preparing a single crystal optical fiber is as described in Example 1, except that the mixed raw material is 5 mol% of Er2O3 doping raw material and 95 mol% of Ga2O3 matrix raw material, and does not contain Eu2O3. Other steps and conditions are consistent with Example 1.

[0049] Compared with Example 1, this comparative example does not contain Eu, resulting in a weakening of the intensity and bandwidth of its absorption band. The diameter of the single crystal optical fiber obtained in this example is 0.6 mm, the length is 171 mm, and the diameter fluctuation of the single crystal optical fiber is 3%.

[0050] Comparative Example 5

[0051] A method for preparing a single crystal optical fiber, as described in Example 1, except that: the specific steps of preparing a source rod and a seed crystal are as follows: first, a matrix raw material and a doping raw material are mixed together, and ground for 12-24 hours, the raw materials are put into a rubber mold to make a round rod, the round rod is put into a cold isostatic press, kept at a pressure of 200Mpa for 5 minutes, and then the pressure is slowly released and taken out, the rubber mold is broken to take out the round rod, and then sintered at 1450°C for 20 hours to obtain a material rod; in addition, one of the material rods is selected, one end is ground to a diameter of 0.4-1mm, as a seed crystal, and the other material rod is used as a source rod. The other steps and conditions are the same as those in Example 1.

[0052] In this comparative example, since there are some pores in the powder after static pressing and the pores are unevenly distributed, the source rod will bend to a certain extent after solid-phase sintering. Before the growth process starts, after the top of the source rod is aligned with the focus to obtain the molten zone, due to the poor coaxiality of the source rod, as time goes by, the lower source rod moves vertically upward, the molten zone gradually deviates from the focus, and the junction between the source rod and the growing crystal fiber becomes skewed. The obtained single crystal optical fibers have cracks, poor crystal fiber collimation, and obvious diameter fluctuations, and poor quality. The diameter of the obtained single crystal optical fiber is 0.6 mm, the diameter fluctuation is 16%, and the length is 164 mm.

[0053] Comparative Example 6

[0054] A method for preparing a single crystal optical fiber is as described in Example 1, except that: after the crystal growth is completed, the laser power is reduced at a rate of 10 W / min, and after the laser is turned off, the furnace is opened after the flowing air is passed for 15 minutes, and the crystal is removed. Then, the grown crystal is heated to 800° C. in a sintering furnace for high temperature annealing and kept at a constant temperature for 10 hours, and the other steps and conditions are the same as in Example 1.

[0055] Due to the lower annealing temperature and faster cooling rate, the thermal stress in this comparative example cannot be eliminated, resulting in crystal cracking and poor quality. The diameter of the obtained single crystal optical fiber is 0.6 mm, the diameter fluctuation is 3%, and the length is 171 mm.

[0056] Comparative Example 7

[0057] A method for preparing a single crystal optical fiber is as described in Example 1, except that the growth atmosphere filled in the furnace is an Ar growth atmosphere, and the other steps and conditions are consistent with Example 1.

[0058] The single crystal optical fibers grown in different atmospheres in this comparative example and Example 1 were analyzed and compared in terms of regional stress analysis, axial stress, and radial stress. The average regional phase difference of the single crystal optical fibers grown in Ar and pure O2 atmospheres was 27 and 18 nm, respectively; the average axial stress of the two crystal fibers of Ar and pure O2 was similar, and the average axial phase difference was 5 and 3 nm, respectively; the average radial stress of the two crystal fibers of Ar and pure O2 was similar, and the average radial phase difference was 38 and 24 nm, respectively; it can be seen that the average stress of the crystal fiber grown in pure O2 atmosphere was lower, and the average axial and radial stresses were lower, and the quality of the crystal fiber grown in pure O2 atmosphere was better.

[0059] Comparative Example 8

[0060] A method for preparing a single crystal optical fiber is as described in Example 1, except that a growth atmosphere (pure O2) is filled into the furnace, the pressure in the furnace is controlled to be 0.01 MPa, and the other steps and conditions are consistent with Example 1.

[0061] Comparative Example 9

[0062] A method for preparing a single crystal optical fiber is as described in Example 1, except that a growth atmosphere (pure O2) is filled into the furnace, the pressure in the furnace is controlled to be 0.05 MPa, and the other steps and conditions are consistent with Example 1.

[0063] Comparative Example 10

[0064] A method for preparing a single crystal optical fiber is as described in Example 1, except that a growth atmosphere (pure O2) is filled into the furnace, the pressure in the furnace is controlled to be 0.08 MPa, and the other steps and conditions are consistent with Example 1.

[0065] The surfaces of single crystal optical fibers grown under different pressures of Comparative Examples 8-10 (0.1MPa, 0.05MPa, 0.08MPa) and Example 1 (0.03MPa) were observed and compared. Since the single crystal optical fiber forms a molten zone due to its own surface tension during the growth process, bubbles are prone to appear in the optical fiber. After observation, it was found that the bubble density at 0.1MPa was the highest, the bubble densities at 0.08MPa and 0.05MPa were similar, and there were no bubbles on the surface of the single crystal optical fiber grown from the seed crystal under a pressure of 0.03MPa. Combined with numerical simulation and analysis of bubbles in the optical fiber, pressure has a significant effect on bubble density. The bubble density and size of the single crystal optical fiber can be effectively reduced under low pressure, and low pressure can make the bubbles escape faster, and the crystal quality of the grown single crystal optical fiber will also be better, thereby achieving the purpose of improving its optical performance.

[0066] Finally, it should be noted that the above-mentioned embodiments only express several implementation methods of the present invention and are not intended to limit the invention. For those skilled in the art, any modification, equivalent replacement, improvement, etc. made without departing from the concept of the present invention should be included in the protection scope of the invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a high thermal conductivity erbium-doped β-phase gallium oxide laser crystal, characterized in that: The following steps are involved: Using Ga2O3 as the matrix material, Er2O3 and Eu2O3 as the doping materials, preparing the source rod and the seed crystal, and then using the laser heating pedestal method to grow the high thermal conductivity erbium-doped β-phase gallium oxide laser crystal; The specific steps of the laser heating base method are as follows: fix the prepared source rod on the feeding device, and fix the prepared seed crystal on the upper pulling device; turn on the mechanical pump to perform vacuum treatment, and then fill the furnace with growth atmosphere, control the furnace to 0.03MPa, adjust the focus of the laser to fall on the center of the top of the source rod, set the laser program, increase the laser power to 60-100W within 15-20 minutes, melt the top of the source rod, and at the same time adjust the control system so that the center of the top cross section of the source rod is located at the laser reflection focus, continue to increase the power to 120-140W, so that it forms a stable hemispherical molten zone, and keep the temperature constant for 3-5 minutes; slowly lower the seed crystal, and adjust the seed crystal to align After the source rod reaches the center of the hemispherical melting zone, it contacts the melting zone and stops descending. After keeping warm for 5-10 minutes, the pulling device is started and the laser power is increased to 145-155W for necking. When the seed crystal diameter shrinks to 0.3-0.5mm, the power is adjusted to 120-130W for shoulder release and equal diameter growth. During the equal diameter growth process, the seed crystal pulling speed is 40-60mm / h, and the source rod feeding speed is 6-10mm / h. When the crystal grows to the required size, the power is gradually increased to 200W, and the crystal is lifted and removed by continuing to pull. After the crystal growth is completed, the laser power is reduced at a rate of 5W / min. After turning off the laser, the furnace is opened after 15 minutes of flowing air and the crystal is removed. The growth atmosphere is pure oxygen.

2. The method according to claim 1, characterized in that: The specific steps of preparing the source rod and the seed crystal are as follows: first, the matrix raw material and the doping raw material are mixed together, and ground for 12-24 hours, and the ground raw material is sintered at 700-800 degrees for 5-10 hours in a muffle furnace, and then taken out and ball-milled again for 12-24 hours; the raw material is loaded into a rubber mold to make a round rod, and the round rod is put into a cold isostatic press and kept at a pressure of 200Mpa for 5 minutes, and then the pressure is slowly released and taken out, the rubber mold is broken to take out the round rod, and then sintered at 1400-1500°C for 15-20 hours to obtain a material rod; in addition, one of the material rods is selected, one end is ground to a diameter of 0.4-1mm as a seed crystal, and the other material rod is used as a source rod.

3. The method according to claim 1, characterized in that: The molar percentages of Er2O3 and Eu2O3 in the raw materials are 10-30 mol% and 0.1-1 mol%.

4. The method according to claim 1, characterized in that: Before crystal growth, the seed crystal and the source rod were placed in anhydrous ethanol for cleaning for 10 minutes, and then placed in an oven for drying at 60° C. for 6 hours.

5. The method according to claim 1, characterized in that: The method also includes a high temperature annealing step, which comprises the following steps: heating the grown crystal to 1200-1300° C. in a sintering furnace for high temperature annealing and maintaining the temperature for 24-36 hours.

6. The method according to claim 2, characterized in that: The length of the material rod is 30-80 mm and the diameter is 1.5-2.0 mm.

7. A high thermal conductivity erbium-doped β-phase gallium oxide laser crystal prepared by the method according to any one of claims 1 to 6.

8. Use of the high thermal conductivity erbium-doped β-phase gallium oxide laser crystal according to claim 7 in a mid-infrared laser.

Citation Information

Patent Citations

  • Gadolinium gallium garnet novel laser crystal activated by erbium ion co-doped with sensitized ion

    CN101378174A

  • Chromium and praseodymium sensitized ions co-doped gadolinium gallium garnet novel laser crystal activated by erbium ions

    CN101619492A